The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1109/iv.2007.148
|View full text |Cite
|
Sign up to set email alerts
|

HANNAH: A Vivid and Flexible 3D Information Visualization Framework

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Since these seminal projects, much research has been dedicated to designing visualization frameworks that employ the increasing power of hardware and leverage our increasing understanding of what makes interaction techniques effective (Troy and Moller, 2004). Recent examples include: Hannah (Einsfeld et al, 2007), a 3D user interface to synthesize desperate data within a single view; Behaviourism (Forbes et al, 2010), a Java/ OpenGL-based framework for creating 2D and 3D visualizations; and EditFlow (Benzaken et al, 2011), an information visualization framework built on top of a database management system. Most recent efforts in visualization framework design are focused on supporting the growing area of information visualization, which does not mesh well with the requirements of real-time simulation-based system.…”
Section: Visualization Frameworkmentioning
confidence: 99%
“…Since these seminal projects, much research has been dedicated to designing visualization frameworks that employ the increasing power of hardware and leverage our increasing understanding of what makes interaction techniques effective (Troy and Moller, 2004). Recent examples include: Hannah (Einsfeld et al, 2007), a 3D user interface to synthesize desperate data within a single view; Behaviourism (Forbes et al, 2010), a Java/ OpenGL-based framework for creating 2D and 3D visualizations; and EditFlow (Benzaken et al, 2011), an information visualization framework built on top of a database management system. Most recent efforts in visualization framework design are focused on supporting the growing area of information visualization, which does not mesh well with the requirements of real-time simulation-based system.…”
Section: Visualization Frameworkmentioning
confidence: 99%
“…For instance, some visual representations are based on abstract representations, such as graphs (Ahmed et al (2006)), trees (Einsfeld et al (2007), Buntain (2008)), and geometrical shapes (Ogi et al (2009), Nagel et al (2008, Meiguins et al (2006)) and others on virtual worlds objects (Baumgärtner et al (2007)). The classification proposed in this chapter provides some initial insight into which techniques are oriented to certain data types, but does not assert that one visual representation is more suitable than others to explore a particular data set.…”
Section: Visual Representations For Visual Data Miningmentioning
confidence: 99%
“…Beale (2007) has demonstrated that using a system which supports the free exploration and manipulation of information delivers increased knowledge even from a well know dataset. Many systems provide a virtual hand or a virtual pointer (Einsfeld et al (2007)), a typical approach used in VE, which is considered as being intuitive as it simulates real-world interaction (Bowman et al (2001)). …”
Section: Visual Explorationmentioning
confidence: 99%
“…Visual languages (such as [37,11]) or general prototyping programming frameworks (such as [24,28]) aim to let developers "sketch" visualization and interaction ideas quickly before deciding whether or not to commit to developing a more robust implementation. Another framework enables the overlap of time-dependent processes with information visualization techniques, allowing users to create "process visualizations" which incorporate dynamic and temporal data [13].…”
Section: Visualization Frameworkmentioning
confidence: 99%